(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The design, development and implementation of every database are mainly to serve as an information hub for organisations. The database is a key factor to the success of most organisations. The process of designing a database usually takes numerous steps which involves the use of various tools and techniques during the design so as to ensure that the database provides data that is of good quality and correct at the same time. This write up is going to contain a reflection on an assignment submitted for the design of a database for a company called courtesy active mobile phones. Various database design tools such as class diagrams use case models and Entity relational diagram were used for the design of the database.